2021
DOI: 10.3389/fmicb.2021.715088
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With Creatine Pyruvate Alters Rumen Microbiota Protein Function in Heat-Stressed Beef Cattle

Abstract: Creatine pyruvate (CrPyr) is a new multifunctional nutrient that can provide both pyruvate and creatine. It has been shown to relieve the heat stress of beef cattle by improving antioxidant activity and rumen microbial protein synthesis, but the mechanism of CrPyr influencing rumen fermentation remains unclear. This study aimed to combine 16S rDNA sequencing and metaproteomics technologies to investigate the microbial composition and function in rumen fluid samples taken from heat-stressed beef cattle treated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In addition to the role of methionine in tissue protein synthesis, methionine can serve as a precursor for synthesis of other amino acids such as taurine, cysteine, apolipoprotein, and can donate its methyl via S-adenosyl methionine, for synthesis of choline, carnitine, creatine, and phospholipids which are all essential for improved skeletal muscle and hepatic lipid metabolism for energy supply especially during reduced supply of glucose. In this study, lower plasma level of methionine in HFE steers was accompanied with higher plasma levels of taurine and creatine, which are known to regulate lipid metabolism in humans and farm animals (da Silva et al, 2014;Karisa et al, 2014;Ibrahim et al, 2019;Li et al, 2021). In a similar study, Karisa et al (2014) reported that plasma concentration of creatine was associated with RFI.…”
Section: Discussionsupporting
confidence: 51%
“…In addition to the role of methionine in tissue protein synthesis, methionine can serve as a precursor for synthesis of other amino acids such as taurine, cysteine, apolipoprotein, and can donate its methyl via S-adenosyl methionine, for synthesis of choline, carnitine, creatine, and phospholipids which are all essential for improved skeletal muscle and hepatic lipid metabolism for energy supply especially during reduced supply of glucose. In this study, lower plasma level of methionine in HFE steers was accompanied with higher plasma levels of taurine and creatine, which are known to regulate lipid metabolism in humans and farm animals (da Silva et al, 2014;Karisa et al, 2014;Ibrahim et al, 2019;Li et al, 2021). In a similar study, Karisa et al (2014) reported that plasma concentration of creatine was associated with RFI.…”
Section: Discussionsupporting
confidence: 51%
“…In previous studies, people have tried almost all feed substitutes and achieved remarkable results, as well as tried different types of additives, which have been proven to improve animal growth performance improving growth and enhancing immunity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, people have tried almost all feed substitutes and achieved remarkable results, as well as tried different types of additives, which have been proven to improve animal growth performance improving growth and enhancing immunity [ 7 , 8 , 9 , 10 ]. Chitin is a natural polymer with high production and biodegradability in nature, second only to cellulose.…”
Section: Introductionmentioning
confidence: 99%